NK cell phenotypic profile during active TB in people living with HIV-evolution during TB treatment and implications for bacterial clearance and disease severity - Maseko, Thando Glory; Rambaran, Santhuri; Ngubane, Slindile; Lewis, Lara; Ngcapu, Sinaye; Hassan-Moosa, Razia; Archary, Derseree; Perumal, Rubeshan; Padayatchi, Nesri; Naidoo, Kogieleum; Sivro, Aida (Scientific reports, 2023)
Natural killer (NK) cells, key effector cells of the innate immune system, play an important role in the clearance and control of Mycobacterium tuberculosis and HIV infections. Here, we utilized peripheral blood specimens from the Improving Retreatment Success CAPRISA 011 study to characterize NK cell phenotypes during active TB in individuals with or without HIV co-infection. We further assessed the effects of TB treatment on NK cell phenotype, and characterized the effects of NK cell phenotypes during active TB on mycobacterial clearance and TB disease severity measured by the presence of lung cavitation. TB/HIV co-infection led to the expansion of functionally impaired CD56 neg NK cell subset. TB treatment completion resulted in restoration of total NK cells, NK cell subset redistribution and downregulation of several NK cell activating and inhibitory receptors. Higher percentage of peripheral CD56 bright cells was associated with longer time to culture conversion, while higher expression of NKp46 on CD56 dim NK cells was associated with lower odds of lung cavitation in the overall cohort and the TB/HIV co-infected participants. Together these results provide a detailed description of peripheral NK cells in TB and TB/HIV co-infection and yield insights into their role in TB disease pathology.